Isolation of bacteriophages infecting Xanthomonas oryzae pv. oryzae and genomic characterization of novel phage vB_XooS_NR08 for biocontrol of bacterial leaf blight of rice - Jain, Lata; Kumar, Vinay; Jain, Sanjay Kumar; Kaushal, Pankaj; Ghosh, Probir Kumar (Frontiers in Microbiology, 2023)
Bacterial leaf blight (BLB) disease of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most destructive diseases worldwide in rice-growing regions. The Ineffectiveness of chemicals in disease management has increased the interest in phage therapy. In this study, we isolated 19 bacteriophages, infecting Xoo, from a rice field, which belonged to phage families Siphoviridae, Myoviridae, and Podoviridae on the basis of electron microscopy. Among 19 phages, Phage vB_XooS_NR08, a member of the Siphoviridae family, expressed antibacterial activity against all Xoo strains tested and did not lyse X. campestris and other unrelated bacterial hosts. Phage NR08 showed more than 80% viability at a temperature range of 4°C–40°C, pH range of 5–9, and direct exposure to sunlight for 2 h, whereas UV light and chemical agents were highly detrimental. In a one-step growth curve, NR08 has a 40-min latent period, followed by a 30-min burst period with a burst size of 250 particle/bacterium. The genome of NR08 is double-stranded DNA, linear having a size of 98,812 bp with a G + C content of 52.9%. Annotation of the whole-genome sequence indicated that NR08 encodes 142 putative open reading frames (ORFs), including one ORF for tRNA, namely, trna1-GlnTTG. Comparative genome analysis of NR08 showed that it shares maximum similarity with Pseudomonas phage PaMx42 (40% query coverage, 95.39% identity, and acc. Length 43,225) and Xanthomonas phage Samson (40% query coverage, 96.68% identity, and acc. Length 43,314). The average alignment percentage (AP) of NR08 with other Xoophages was only 0.32 to 1.25 since the genome of NR08 (98.8 kb) is almost double of most of the previously reported Xoophages (43–47 kb), thus indicating NR08 a novel Xoophage. In in vitro bacterial challenge assay, NR08 showed bacteriostasis up to 24 h and a 99.95% reduction in bacterial growth in 48 h. In rice pot efficacy trials, single-dose treatment of NR08 showed a significant reduction in disease up to 90.23% and 79.27% on 7 and 21 dpi, respectively. However, treatment using 2% skim milk-supplemented phage preparation was significantly less effective as compared to the neat phage preparation. In summary, this study characterized a novel Xoophage having the potential as a biocontrol agent in the mitigation of BLB in rice.